Séquence sédimentaire du secteur aval de la rivière Coppermine, Territoires du Nord-Ouest - Bruneau, Hélène C. (Géographie physique et Quaternaire, 1985)
The study of 31 sections along the Coppermine River, between September and Coppermine mountains and Coronation Gulf, makes it possible to understand the postglacial history of the area. Following déglaciation, the sea invaded the depressed coastal lowlands and the Coppermine River resumed its course northward. Its high sediment load originating from the sediment-laden glacial meltwaters and the reworked Glacial Lake Coppermine deposits resulted in an important sedimentation in the postglacial sea. Sedimentation in the deeper areas of the sea left thick deposits of silt and clay rythmites. These rythmites owe their origin to turbidity currents. A 30 m-thick diamicton is interbedded with the rythmites. It is interpreted as the result of a number of debris flows generated by liquefaction of Glacial Lake Coppermine varves early in the region's postglacial history. These deposits are gradually overlaid by coarser beach or deltaic sediments, up to gravel and boulder size. This coarsening-upward sequence is typical of sedimentation in an offlap marine phase. The 14C dates suggest a minimum age of 10,000 BP for the postglacial marine phase. L'étude des sédiments exposés dans 31 coupes le long du cours inférieur de la rivière Coppermine, entre les monts September et Coppermine et le golfe du Couronnement, a permis de reconstituer l'évolution postglaciaire de la région. Après le retrait des glaces, Ia mer a envahi la zone côtière déprimée par glacio-isostasie sous le niveau marin. La déglaciation a aussi permis à la rivière Coppermine de reprendre son cours vers le nord. Or, celle-ci transportait d'énormes quantités de sédiments qui lui étaient fournies d'une part par les eaux de fonte provenant des masses de glace en décrépitude et, d'autre part, par le remaniement des sédiments du lac glaciaire Coppermine. La sédimentation dans les parties relativement profondes de la mer postglaciaire est représentée par d'importants dépôts de silt et d'argile rythmés. Ces rythmites résultent d'une mise en place par des courants de ...